MOLECULAR CHARACTERIZATION, PHYTOCHEMICAL AND DOCKING STUDIES OF MOSQUITO REPELLENT COMPOUNDS IN OCIMUMBASILICUM LINN.VAR. PILOSUM (WILLD.) - BENTH. - VENU GOPAL GADDAGUTI; REPALLE SREE DEEPTHI; ALLU PRASADA RAO (International Journal of Pharma and Bio Sciences, 2013)
Many species of Ocimum reported to exhibit insecticidal and insect repellent properties. In the present investigation, molecular characterization of Ocimum basilicum Linn. var. pilosum (willd)- Benth was carried out with EST SSR markers and efficiently demarcated the O.basilicum Linn. var. pilosum (willd)- Benth from other Ocimum varieties. The leaf extract of O.basilicum Linn. var. pilosum (willd)- Benth was analyzed by GC-MS and 15 compounds were identified. Compounds which are structurally similar to the DEET were docked with Schrodinger mastero software. n-Hexa decanoic acid and , 4H-1-Benzopyran-4-One,5-Hydroxy-6,7-Dimethoxy-2-(4-Methoxyphenyl) were shown good docking scores with mosquito odorant binding protein 3N7H. N-Hexa decanoic acid present in O.basilicum Linn. var. pilosum (willd)- Benth found to be an ideal candidate for development of another potential mosquito repellent.